ABDIMAS: WADAH KOLABORASI DOSEN UNMAS DENPASAR DENGAN WARGA SEKOLAH SDN 1 PEREAN KANGIN - Ekayanti, Ni Wayan; Puspawati, Dewa Ayu; Sardi, Ni Wayan Arni (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
The main purpose of this community science and technology program is to improve health and optimize the potential of SDN 1 Perean Kangin in learning activities. There are a number of problems that SDN 1 Peran Kangin has, namely: 1) there are still many students who cannot brush their teeth properly, 2) students cannot wash their hands according to the guidelines of the Department of Health in the school yard and 4) there is no trash can classroom. To overcome these problems, technology transfer is needed through counseling activities, and demonstrations in the field. From the activities that have been done, the results are 1) students are able to brush their teeth properly because of the direction and demonstration from the dentist 2) students are able to wash their hands according to the MOH instructions, 3) the plants in the school yard have labeled the Latin name of the plant , 4) each class room has organic and non-organic bins.